Pulmonary artery banding in patients with functional single ventricle associated with pulmonary hypertension. (19th May 2021) - Li, Gang; Zhang, Han; Fan, Xiangming; Su, Junwu
ABSTRACT: Background : To assess the impact of our surgical strategy for the treatment of patients with functional single ventricle and pulmonary hypertension, especially in patients>24 months old. Methods We retrospectively analyzed the clinical data of 97 patients with functional single ventricle and pulmonary hypertension undergoing pulmonary artery banding (PAB) in our hospital between April 2010 and December 2018. The surgical results, transition to Glenn operation and subsequent transition to Fontan operation were analyzed. Results: The 97 patients underwent PAB included 34 patients>24 months old, hospital mortality was 2.1% (2/97). 62 patients underwent the second-stage Glenn operation, and 21 patients underwent third-stage Fontan operation. On competing risk analysis, at 80 months after PAB, 81% had undergone the Glenn operation, and 13% were awaiting the Glenn operation. At 35 months after the Glenn operation, 2% of patients had died, 63% had undergone the Fontan operation, and 36% were awaiting the Fontan operation. Conclusion: PAB is an acceptable strategy for patients with functional single ventricle associated with pulmonary hypertension. Outcomes and results of subsequent Glenn and Fontan procedures are generally good included patients>24 months. Accompanied with unbalanced atrioventricular septal defect for lower ratio of transition to Glenn and Fontan operation.